Emerging and re-emerging infections: threat to the world - Veerapalli, Harish (International Journal Of Community Medicine And Public Health, 2020)
Emerging and reemerging infections are a huge threat to the human race which can destabilize humans from the roots. It is a global problem and not a problem for any single country. 15 million deaths occur annually across the globe due to infections, and 12% of them are due to emerging pathogens. These infections are returning every year with an increased incidence rate and higher virulence. In the present era of globalization and living conditions, such as living in crowded areas increases the potential for the spread of these emerging and reemerging infections, eventually affecting public health. The most prominent challenge that poses in the face of public health officials is the achievement of global preparedness to combat these infections. Aggressive research is needed in this field to help being prepared for an attack by these infections. Global organizational cooperation, international research funding, and poverty reduction are very much necessary for taking measures against these infections.